The Influence of Library Utilization and Social Environment on the Level of Economic Literacy in Class XI IPS Students at MA Nurul Huda Sidoarjo - Rizky Pradana Putra; Heni Purwa Pamungkas; Muhammad Abdul Ghofur (IKIP Widya Darma Surabaya, 2023)
This study aims to determine the effect of library utilization on the level of economic literacy of students of class XI IPS at MA Nurul Huda Sidoarjo. The influence of the social environment on the level of economic literacy of students of class XI IPS at MA Nurul Huda Sidoarjo. The subjects of this study were 72 students of social science class at MA Nurul Huda Sidoarjo. Data collection in this study used a questionnaire by making the entire study population into a sample or saturated sample. The method used is quantitative descriptive. Data analysis uses multiple linear regression. Research results showed that the variable utilization of the library and social environment simultaneously has no significant effect on the level of economic literacy of students in class XI IPX MA Nurul Huda Sidoarjo. The magnitude of the effect of the use of variables X1 and X2 on the variable Y uses the coefficient of determination by looking at the SPSS model summary output display. Based on the results of the simultaneous significance test (f test) in the significance table, the value is 0.425 above the significance requirement of 0.05. Based on the basis of simultaneous test decision making in regression analysis, it can be concluded that the variable utilization of library (X1) and social environment (X2) does not significantly influence the level of economic literacy of students in class XI IPS MA Nurul Huda Sidoarjo.